Busted sanctions explaining why economic sanctions fail - Early, Bryan R. (Stanford University Press, 2015)
Powerful countries like the United States regularly employ economic sanctions as a tool for promoting their foreign policy interests. Yet this foreign policy tool has an uninspiring track record of success, with economic sanctions achieving their goals less than a third of the time they are imposed. The book offers the first comprehensive explanation for why different types of sanctions busting occur and reveals the devastating effects it has on economic sanctions' chances of success.